2022
DOI: 10.1038/s41893-022-00949-x
|View full text |Cite
|
Sign up to set email alerts
|

Insect pest management with sex pheromone precursors from engineered oilseed plants

Abstract: Pheromones have become an environmentally friendly alternative to conventional insecticides for pest control. Most current pheromone-based pest control products target lepidopteran pests of high-value crops, as today’s manufacturing processes cannot yet produce pheromones at low enough costs to enable their use for lower-value crops, especially commodity crops. Camelina sativa seeds genetically modified to express (Z)-11-hexadecenoic acid, a sex pheromone precursor of several moth species, provided the oil fro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Pheromone yields from alternative species in which production is limited to specific organs might also be tested. For example, precursors of Lepidopteran sex pheromones have recently been produced in the seeds of field-grown transgenic Camelina sativa (false flax) (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pheromone yields from alternative species in which production is limited to specific organs might also be tested. For example, precursors of Lepidopteran sex pheromones have recently been produced in the seeds of field-grown transgenic Camelina sativa (false flax) (Wang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…They also produce many metabolic precursors and cofactors allowing the facile reconstruction of metabolic pathways often without the need to engineer host genes and pathways (Patron, 2020; Stephenson et al, 2020). For example, precursors of Lepidopteran sex pheromones have been produced in field-grown transgenic Camelina sativa (false flax) (Wang et al, 2022)), while biosynthesis of the pheromone molecules has been demonstrated in other plant species (Ding et al, 2014; Mateos-Fernández et al, 2021; Xia et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…54 A pheromone-based bio-insecticide, for example, that is aggressive in stopping the spread of a specific insect-pest species is only effective against that pest species. 55 Other pests aren't affected by it. It is vital to remember that synthetic chemicals are dangerous xenobiotics, even though they offer a far broader spectrum of activity.…”
Section: The Significance Of Agrochemicals In Modern Agriculturementioning
confidence: 99%
“…4 Pheromones can reduce or prevent pests through monitoring, mass trapping, and mating disruption. 5 However, they cannot be used efficiently in the field for a long time period due to the volatility and chemical instability of most pheromones. 6 The current carriers (such as rubber, polyethylene plastic, etc.)…”
mentioning
confidence: 99%